Numerical Simulation of Masonry Panels - Auciello, N.M.; Ercolano, A. (Engineering Transactions, 1997)
In the present paper, a new linear complementary formulation for contact problems under Coulomb law of friction (which takes into consideration the rigid body modes) is presented. Moreover, a finite element model for the numerical simulation of masonry panels is developed and a technique for fast updating of the interface elements is reported. The masonry is considered as a composite material produced by the inclusion of bricks into the matrix of mortar. The two components are supposed to be perfectly linear elastic, the unilateral contact being restricted to the blocks-mortar interfaces. An example of masonry panel is reported.